Documentation of Transhumance Practices in Southern Region of Mali - International Livestock Research Institute; Association Malienne d'Eveil au Développement Durable (International Food Policy Research Institute, 2017)
This study contains data from individual household survey on different transhumance practices; local perceptions on benefits and constraints of these practices; and the effects of these practices on natural resource management.